Get Backed: Craft Your Story, Build the Perfect Pitch Deck, and Launch the Venture of Your Dreams - Beahr, Evan (Harvard Business Review Press, 2015)
What’s in the book? The original pitch decks and fundraising strategies of 15 ventures that raised over